Design and Construction of Soyabean Milk Maker - Winanda Pardhanu; Saipul Bahri Daulay; Adian Rindang (Universitas Sumatera Utara, 2016)
The process in making soya bean to be soya milk is an interesting thing to know. This research was held to design, to construct, to test, and to analyze economic value of soya bean milk maker. The parameter observed were effective capacity, yield percentage, organoleptic’s test and economic analysis.Based on this research, it was summerized that the effective capacity of this equipment was 6,18 kg/hour. Yield percentage was 64,4%. Basic cost from first year to fifth year were Rp 2.082/kg, Rp 1.920/kg, Rp 1.866,4/kg, Rp 1.839,26 dan Rp 1.823,12/kg. Break even point was 350,85 kg/year. Net present value with 8% rate was Rp 127.554.735,4 and internal rate of return was 34,4%. Keywords: Soya bean, milk, effective capacity, yield percentage, economic analysis